Mrs Dalloway and The Awakening : tracing a relation between the growing feminist movements and modern fictions from Late 19th to 20th Century American and English literary landscape - Habiba, Ummay (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015.